2000
DOI: 10.1038/sj.jp.7200320
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Postdischarge Complications by Predischarge Event Recordings in Infants With Apnea of Prematurity

Abstract: OBJECTIVE:To determine whether predischarge event recording (PDER) can accurately identify preterm infants with resolving apnea of prematurity (AOP) at risk for postdischarge complications. DESIGN:PDER was performed on infants with resolving AOP on caffeine, ready for discharge. The outcome of infants with normal recordings was compared with that of infants with abnormal recordings. Follow-up data were obtained for outcome. RESULTS:Of the 106 infants, 74 had a normal PDER and 32 had an abnormal PDER (apneas la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…These events may have been self-resolved or occurred during feeding or stressors such as immunization, ( 39 ) Most infants were sent home without a monitor and very few were readmitted to our hospital within 2 months for apnea or ALTE, which is in keeping with other reports. ( 40 ) Our unit protocol of discharging infants after a week free of needing stimulation to resolve an apneic spell has not changed based on our studies to date, and further work in larger patient populations is needed to establish criteria for safe NICU discharge, since the cost of additional hospital days simply for an “apnea countdown” is substantial. ( 41 )…”
Section: Resolution Of Apneamentioning
confidence: 99%
“…These events may have been self-resolved or occurred during feeding or stressors such as immunization, ( 39 ) Most infants were sent home without a monitor and very few were readmitted to our hospital within 2 months for apnea or ALTE, which is in keeping with other reports. ( 40 ) Our unit protocol of discharging infants after a week free of needing stimulation to resolve an apneic spell has not changed based on our studies to date, and further work in larger patient populations is needed to establish criteria for safe NICU discharge, since the cost of additional hospital days simply for an “apnea countdown” is substantial. ( 41 )…”
Section: Resolution Of Apneamentioning
confidence: 99%
“…75 Predischarge event recording is sometimes used as a way to evaluate the extent of persisting apnea episodes and determine the need for a home apnea monitor. 6,76 Event-recording monitors register heart rate, respiratory rate, pulse oximetry, and, in some cases, nasal airflow oscillimetry, providing more objective data than can be obtained from nursing documentation. 6,76 In the absence of event recordings, nursing documentation based on clinical observations of apnea and bradycardia events is the primary means of formulating discharge decisions for individual infants.…”
Section: Apnea Resolution and Discharge Planningmentioning
confidence: 99%
“…6,76 Event-recording monitors register heart rate, respiratory rate, pulse oximetry, and, in some cases, nasal airflow oscillimetry, providing more objective data than can be obtained from nursing documentation. 6,76 In the absence of event recordings, nursing documentation based on clinical observations of apnea and bradycardia events is the primary means of formulating discharge decisions for individual infants. 75 When infants are otherwise ready for discharge (have achieved full oral feedings, are maintaining body temperature in an open crib, etc), persistence of apnea and/or bradycardia will delay discharge.…”
Section: Apnea Resolution and Discharge Planningmentioning
confidence: 99%
“…Many preterm infants experience pauses in breathing (‘apnoea’) and drops in blood oxygen saturation levels. As an infant matures towards term corrected age, these events become less frequent, however, clinically unapparent events may still occur up to and beyond discharge home . The long‐term implications for infants experiencing these persistent respiratory events are not completely clear.…”
Section: Introductionmentioning
confidence: 99%
“…The long‐term implications for infants experiencing these persistent respiratory events are not completely clear. Some studies have shown an association between episodes of intermittent hypoxia and both reduced initial weight gain after discharge and longer term neurodevelopmental delay . Therefore, when assessing a preterm infant's readiness for discharge from the neonatal intensive care unit (NICU), it is important to establish that the infant is stable from a cardiorespiratory perspective.…”
Section: Introductionmentioning
confidence: 99%